A strata living in peninsula Malaysia: Legal and human managements issues - Sufian, Azlinor; Mohamad, Nor Asiah (2009)
Strata Titles Act 1985 has been introduced in order to cater the needs to have a proper laws and regulations governing the strata living. The enforcement of the Act has contributed in many ways in managing the strata building in which strata living is one of the new features in urban development. Under the Strata Title Act 1985, developers who develop strata buildings are assigned with duties and obligations to manage the strata building efficiently and professionally. Besides that the responsibilities to manage strata buildings are not only impose on developers but these responsibilities shall be shared by the house owners too. This article analyses the problems in managing the strata building inPenisula Malaysia and how those problems are tackled by the enforcement of two main statutes relating to strata title i.e. Strata Title Act 1985 and Building and Common Property (Maintenance and Management) Act 2007 ("BCPMMA") This article then seeks to see to what extent the existing laws and regulations in Penisula Malaysia facilitate the developers and purchasers as well as the local authority to regulate the living in strata buildings. It will focus on the rights and responsibilities of the developers that developed the strata projects, the community living within the strata as well as the government in managing the affairs within the strata. Discussions on these points are expected to reveal whether the existing laws are sufficient to manage the strata building. Discussions in this paper will involve various types of strata developed in Penisular Malaysia, for instance condominiums, apartments, flats, serviced apartments and gated communities.